High-efficiency medical image encryption method based on 2D Logistic-Gaussian hyperchaotic map - Lai, Qiang; Hu, Genwen; Erkan, Uǧur; Toktas, Abdurrahim (Applied mathematics and computation, 2023)
•A new hyperchaotic map with wide range of hyperchaos is presented.•A new chaos-based medical image encryption algorithm is established.•The secure performance of the proposed algorithm is thoroughly analyzed. This paper designs a new medical image encryption scheme based on a new hyperchaotic map, which exhibits excellent security and high efficiency that can be applied to medical images of distinctive presentation formats. Firstly a two-dimensional Logistic-Gaussian hyperchaotic map (2D-LGHM) with a wide range of hyperchaos is constructed, and performance test metrics reveal that it has better ergodicity and unpredictability. Based on 2D-LGHM, a new medical image encryption scheme with permutation and multi-directional pixels substitution processes are established. The chaotic sequence is efficiently used to break the correlation between adjacent pixels and change the global pixel value absolutely. By means of the test of diverse medical images, the results display that the scheme has high robustness and effectiveness that can defense against different security attacks and data loss.